Prevalence and factors associated with child marriage, a systematic review - Asma Pourtaheri; Seyedeh Belin Tavakoly Sany; Monavvar Afzal Aghaee; Hamideh Ahangari; Nooshin Peyman (BMC, 2023)
Abstract Background Girl child marriage is increasingly recognized as a critical barrier to global public health and gender discrimination. There are still more gaps in the global rate of child marriage and the underlying factors. Thus, the present systematic review aimed to explore the prevalence of child marriage and the underlying factors. Methods A comprehensive search was conducted for all English-language studies that measured the prevalence of child marriage and its correlates from 2000 to March 2022, indexed in PubMed, Scopus, Web of Science, Poplin, and Google Scholar databases. Child marriage is defined as marriage under the age of 18. In the present study, Joanna Briggs' quality assessment checklist was used for data collection. Two independent reviewers reviewed all the articles. Results In total, 34 eligible prevalence articles and 14 trend articles were included in the study with data from 127,945 participants. The prevalence of child marriage ranged between 1.8% to 90.85%. In most studies, the trend of child marriage was decreasing. The most important individual factors include the respondent's education and occupation, interpersonal factors such as the education and occupation of parents and husband, family size and type. Community factors include socioeconomic status, region, residence, ethnicity, and religion at the social level. Conclusion Despite a central focus of research and policies on interventions that decrease child marriage, this phenomenon is still prevalent in many places. Therefore, further specific interventions are required to improve education, reduce poverty and inequality. This may help achieve the 2030 Sustainable Development Goals.